Tsukamurella tyrosinosolvens intravascular catheter-related bacteremia in a haematology patient: a case report - Karunakaran, R.; Halim, H.A.; Ng, K.P.; Hanifah, Y.A.; Chin, E.; Jaafar, F.L.; AbuBakar, Sazaly (2011)
Tsukamurella spp. are a rare but important cause of intravascular catheter-related bacteremia in immunocompromised patients. The organism is an aerobic, Gram-positive, weakly acid-fast bacillus that is difficult to differentiate using standard laboratory methods from other aerobic actinomycetales such as Nocardia spp., Rhododoccus spp., Gordonia spp., and the rapid growing Mycobacterium spp. We report a case of Tsukamurella tyrosinosolvens catheter-related bacteremia in a 51-year-old haematology patient who responded to treatment with imipenem and subsequent line removal. 16srRNA sequencing allowed for the prompt identification of this organism.